Titanium dioxide for fluorocarbon coating and preparation method thereof

By using a multi-layer envelope structure in fluorocarbon coatings to enhance the weather resistance and dispersion of titanium dioxide, the problem of insufficient weather resistance and dispersion of titanium dioxide in existing fluorocarbon coatings is solved, and the long-term effect and stability of the coating are achieved.

CN116496643BActive Publication Date: 2025-03-25LOMON BILLIONS GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310267373.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-17
Publication Date
2025-03-25
Estimated Expiration
2043-03-17

AI Technical Summary

Technical Problem

The weather resistance and dispersion of titanium dioxide in existing fluorocarbon coatings are insufficient, resulting in the paint being easily yellowed, aged and powdered during use.

Method used

By forming a multi-layer envelope structure on the surface of the titanium dioxide substrate, including an active dense silicon oxide film layer with hydroxyl groups on the outer layer, a dense aluminum silicate film layer, a dense silicon oxide film layer and a Bayerite and Boehmite composite alumina film layer, the weather resistance and dispersion of the titanium dioxide powder are enhanced.

Benefits of technology

It significantly improves the weather resistance and dispersion of titanium dioxide, extends the service life of the paint, and avoids the yellowing and powdering of the paint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116496643B_ABST
    Figure CN116496643B_ABST
Patent Text Reader

Abstract

The present invention discloses a titanium dioxide for fluorocarbon coatings and a preparation method thereof, wherein the titanium dioxide comprises a titanium dioxide substrate and a coating layer located on the surface of the titanium dioxide substrate, wherein the coating layer comprises, from the inside to the outside, an outer layer of an active dense silicon oxide film layer having hydroxyl groups, a dense aluminum silicate film layer, a dense silicon oxide film layer, and a Bayerite and boehmite composite aluminum oxide film layer. The titanium dioxide provided by the present application has ultra-high weather resistance and dispersibility, and is suitable for use in fluorocarbon coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pigment preparation, and particularly relates to titanium dioxide for fluorocarbon coatings and a preparation method thereof. Background Art

[0002] Among various coatings, fluororesin coatings offer exceptional properties due to the high electronegativity of the introduced fluorine element and the strong carbon-fluorine bond. These include weather resistance, heat resistance, low-temperature resistance, chemical resistance, and unique non-stick and low-friction properties. After decades of rapid development, fluororesin coatings have gained widespread application in various fields, including construction, the chemical industry, electrical and electronics, machinery, aerospace, and household products. They have become the highest-performing coating brand after high-performance coatings such as acrylic, polyurethane, and silicone coatings.

[0003] Titanium dioxide is non-toxic, has the best opacity, the best whiteness and brightness, and is considered to be the best performing inorganic white pigment in the world. It accounts for 80% of all white pigments used, of which more than 50% is used in coatings. The lattice of titanium dioxide inevitably has some defects during its growth process. Under the condition of light, it absorbs the higher energy ultraviolet rays and causes electron transition. 4+ Become Ti 3+ Release free radicals, and under the action of water and oxygen, Ti 3+ Become Ti 4+ Free radicals are released, which continuously degrade the resin matrix, causing the coating to yellow, age and chalk.

[0004] Fluorocarbon is a coating with high weather resistance, so fluorocarbon coatings have higher weather resistance requirements for titanium dioxide.

[0005] Based on this, the present invention proposes a method for preparing titanium dioxide with high weather resistance to meet the demand of fluorocarbon coatings for titanium dioxide with high weather resistance. Summary of the Invention

[0006] The purpose of the present invention is to provide a titanium dioxide for fluorocarbon coatings and a preparation method thereof in order to solve the deficiencies of the prior art.

[0007] The purpose of the present invention is achieved by the following technical solutions:

[0008] A titanium dioxide for fluorocarbon coatings comprises a titanium dioxide substrate and a coating layer located on the surface of the titanium dioxide substrate. The coating layer comprises, from the inside to the outside, an outer layer of an active dense silicon oxide film layer having hydroxyl groups, a dense aluminum silicate film layer, a dense silicon oxide film layer, and a byerite and boehmite composite aluminum oxide film layer.

[0009] Preferably, the outer layer of the active dense silicon oxide film layer having hydroxyl groups is formed by the following steps: adding a silicate source to a titanium dioxide-based material slurry at a temperature of 90 to 98°C and a pH of 9.5 to 10.6, then adjusting the pH to 9.3 to 9.5, and forming the outer layer of the active dense silicon oxide film layer having hydroxyl groups after homogenization.

[0010] Preferably, the amount of the silicic acid source used is 1.2-1.8% of the mass of the titanium dioxide substrate, calculated as silicon dioxide.

[0011] Preferably, the dense aluminum silicate film layer and the dense silicon oxide film layer are formed by the following steps: an aluminum source and an excess silicate source are added in parallel to a titanium dioxide-based material slurry covering the outer active dense silicon oxide film layer having hydroxyl groups, and then the pH is adjusted to allow the aluminum silicate to mature and deposit to form a dense aluminum silicate film layer; the incompletely reacted silicate source is adjusted again to allow silicon oxide to be deposited to form the dense silicon oxide film layer.

[0012] Preferably, the amount of the silicic acid source, calculated as silicon dioxide, is 0.5 to 3.2% of the mass of the titanium dioxide substrate; the amount of the aluminum source, calculated as aluminum oxide, is 0.1 to 1.5% of the mass of the titanium dioxide substrate.

[0013] Preferably, the amount of the aluminum source and the silicate source used is calculated as Al2O3:SiO2 mass ratio ≤0.56.

[0014] Preferably, the pH of the aluminum source and excess silicate source in co-flow is maintained at 9.3-10.2, the pH of aluminum silicate aging deposition is 9.6-10.2; and the pH of silicon oxide deposition is 5.0-7.0.

[0015] Preferably, the bayerite and boehmite composite alumina film layer is formed by the following steps: adding an aluminum source to the titanium dioxide-based material slurry coated with the outer layer of active dense silicon oxide film layer with hydroxyl groups, dense aluminum silicate film layer, and dense silicon oxide film layer, adjusting the pH to deposit bayerite-type alumina, and then adjusting the pH to deposit boehmite-type alumina to form the bayerite and boehmite composite alumina film layer; the amount of the aluminum source used is ≤0.9% of the mass of the titanium dioxide substrate in terms of alumina.

[0016] Preferably, the pH of the byerite-type alumina deposition is 9.5-11.7, and the pH of the boehmite-type alumina deposition is 7.0-8.5; and the coating of the byerite and boehmite composite alumina film is carried out at 45-65°C.

[0017] The method for preparing titanium dioxide for fluorocarbon coatings as described above comprises the following steps:

[0018] A titanium dioxide-based material slurry is sequentially coated with an outer layer of an active dense silicon oxide film layer having hydroxyl groups, a dense aluminum silicate film layer, a dense silicon oxide film layer, and a Bayerite and boehmite composite aluminum oxide film layer to obtain the titanium dioxide for fluorocarbon coatings.

[0019] Preferably, the coating method of the active dense silicon oxide film layer having hydroxyl groups on the outer layer is: adding a silicic acid source to a titanium dioxide-based material slurry at a temperature of 90 to 98° C. and a pH of 9.5 to 10.6, then adjusting the pH to 9.3 to 9.5, and forming the active dense silicon oxide film layer having hydroxyl groups on the outer layer after homogenization;

[0020] The coating method of the dense aluminum silicate film layer and the dense silicon oxide film layer is as follows: an aluminum source and an excess silicate source are added in parallel to a titanium dioxide-based material slurry coated with the outer active dense silicon oxide film layer having hydroxyl groups, and then the pH is adjusted to ripen and deposit the aluminum silicate to form a dense aluminum silicate film layer; the uncompletely reacted silicate source is reacted by adjusting the pH again to deposit silicon oxide to form the dense silicon oxide film layer;

[0021] The coating method of the Bayerite and boehmite composite alumina film layer is as follows: adding an aluminum source to a titanium dioxide-based material slurry coated with the outer layer of active dense silicon oxide film layer having hydroxyl groups, dense aluminum silicate film layer, and dense silicon oxide film layer, adjusting the pH to deposit Bayerite-type alumina, and then adjusting the pH to deposit boehmite-type alumina to form the Bayerite and boehmite composite alumina film layer; the amount of the aluminum source used is ≤0.9% of the mass of the titanium dioxide substrate in terms of alumina.

[0022] Preferably, the preparation method further comprises:

[0023] S1. Take a titanium dioxide-based material slurry, adjust the temperature to 90-98°C and the pH to 9.5-10.6; add a silicic acid source, then adjust the pH to 9.3-9.5, and homogenize to form an outer layer of an active dense silicon oxide film with hydroxyl groups;

[0024] S2. An aluminum source and a silicate source are added in parallel, wherein the amount of the aluminum source and the silicate source is Al2O3: SiO2 mass ratio ≤ 0.56, and the pH of the parallel flow is maintained at 9.3 to 10.2, and then the pH is adjusted to 9.6 to 10.2, and a dense aluminum silicate film layer is formed after homogenization;

[0025] S3. Adjust the pH to 5.0-7.0, and after homogenization, the unreacted silicic acid source in step S2 is deposited to form a dense silicon oxide film;

[0026] S4. Add an aluminum source, adjust the pH to 9.5-11.7, adjust the pH to 7.0-8.5 after homogenization, and homogenize again to form a byerite and boehmite composite aluminum oxide film; the amount of the aluminum source used is ≤0.9% of the mass of the titanium dioxide substrate in terms of aluminum oxide.

[0027] The titanium dioxide provided in this application has ultra-high weather resistance and dispersibility, and is suitable for use in fluorocarbon coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a scanning electron microscope image of the titanium dioxide sample provided in Example 1 of the present application;

[0029] Figure 2 This is a scanning electron microscope image of the titanium dioxide sample provided in Example 2 of the present application;

[0030] Figure 3 This is a scanning electron microscope image of the titanium dioxide sample provided in Example 3 of the present application;

[0031] Figure 4 This is a scanning electron microscope image of the titanium dioxide sample provided in Example 4 of the present application;

[0032] Figure 5 is a scanning electron microscope image of the titanium dioxide sample provided in Example 5 of the present application;

[0033] Figure 6 is a scanning electron microscope image of the titanium dioxide sample provided in Example 6 of the present application;

[0034] Figure 7 This is a scanning electron microscope image of the titanium dioxide sample provided in Comparative Example 1 of the present application;

[0035] Figure 8 This is a scanning electron microscope image of the titanium dioxide sample provided in Comparative Example 2 of this application. DETAILED DESCRIPTION

[0036] The present invention provides a titanium dioxide for fluorocarbon coatings, characterized in that it includes a titanium dioxide substrate and a coating layer located on the surface of the titanium dioxide substrate, wherein the coating layer includes, from the inside to the outside, an outer layer of an active dense silicon oxide film layer having hydroxyl groups, a dense aluminum silicate film layer, a dense silicon oxide film layer, and a bayerite and boehmite composite aluminum oxide film layer.

[0037] Silica-alumina coating is a common coating method for titanium dioxide, which can improve its weather resistance and dispersibility. Conventional silica deposition generally involves adding a silicon source such as sodium silicate or potassium silicate to a titanium dioxide-based material slurry. The pH is then slowly adjusted to a weakly acidic state, allowing silica to slowly deposit to form a uniform, dense silica film. This masks the titanium dioxide's lattice defects and improves its weather resistance. Aluminum salts and a pH adjuster are then added concurrently to the surface of the silica film, maintaining a pH between 7.0 and 9.0. This forms a loose boehmite-alumina layer, improving the dispersibility of the titanium dioxide. However, the weather resistance and dispersibility of conventionally treated titanium dioxide are insufficient for use in fluorocarbon coating systems.

[0038] On this basis, the present application first improves the conventional dense silicon oxide film layer into an activated dense silicon oxide film layer-dense aluminum silicate film layer-dense silicon oxide film layer, wherein the inner layer of the activated dense silicon oxide film layer is tightly bonded to the surface of titanium dioxide, and the outer layer is full of active hydroxyl groups, which can be well bonded to the dense aluminum silicate film layer, and the outer layer is wrapped with the dense silicon oxide film layer; the combination of the three film layers forms an ultra-dense photocatalytic shielding film layer, which effectively eliminates the photocatalytic reaction caused by the lattice defects of titanium dioxide under ultraviolet light irradiation and improves the weather resistance of titanium dioxide. Secondly, the conventional aluminum oxide film layer is improved into a bayerite and boehmite composite aluminum oxide film layer, wherein the bayerite aluminum oxide film layer has a high hydroxyl content compared to boehmite aluminum oxide, which significantly improves the dispersibility of titanium dioxide, and can reduce the amount of aluminum coating, thereby improving the hiding power and hue of the product. Therefore, the titanium dioxide provided by the present application has ultra-high weather resistance and dispersibility, and is suitable for use in fluorocarbon coatings.

[0039] Preferably, the outer layer of the active dense silicon oxide film having hydroxyl groups is formed by the following steps: adding a silicic acid source to a titanium dioxide-based material slurry at a temperature of 90-98°C and a pH of 9.5-10.6, then adjusting the pH to 9.3-9.5, and homogenizing to form the outer layer of the active dense silicon oxide film having hydroxyl groups. Preferably, the amount of the silicic acid source used, calculated as silicon dioxide, is 1.2-1.8% of the mass of the titanium dioxide substrate.

[0040] Conventional titanium dioxide-based material slurry, whether it is sulfuric acid method or chloride method-based material slurry, generally has a neutral or acidic pH. If a silicate source is directly added, it is easy to accumulate into agglomerates under neutral and acidic conditions. Therefore, the pH is first adjusted to 9.5-10.6.

[0041] After adding silicon source to titanium dioxide-based material slurry with pH of 9.5-10.6, due to the high pH, ​​generally >10, the pH is adjusted to 9.3-9.5 by dilute acid. Under this pH condition, the generation rate of silicic acid is slow, forming a dense silicon oxide film. And due to the high pH of the environment, OH - The concentration is high, and the outer layer of the dense silicon film is easy to adsorb OH - , forming a dense silicon film with a large number of active hydroxyl groups, while conventional silicon oxide deposition is carried out under acidic conditions, where the formation of silicic acid is faster and the density is poor. + High concentration, OH - The concentration is low and there are no active hydroxyl groups on the surface of the silicon film.

[0042] Preferably, the dense aluminum silicate film layer and the dense silicon oxide film layer are formed by the following steps: in a titanium dioxide-based material slurry coated with an outer layer of an active dense silicon oxide film layer having hydroxyl groups, an aluminum source and an excess silicate source are added in parallel, and then the pH is adjusted to allow the aluminum source to fully react to generate aluminum silicate, which is then aged to form a dense aluminum silicate film layer; as the aluminum silicate film layer is formed, under aging conditions, the incompletely reacted silicate source is freed and adsorbed onto the surface of the aluminum silicate film layer, and the pH is subsequently adjusted again, and the excess silicate source adsorbed on the surface of the aluminum silicate film layer is deposited to form a dense silicon oxide film layer located on the outermost side. The excess here refers to the amount of silicate source exceeding the theoretical stoichiometric requirement for reacting with the aluminum source to generate aluminum silicate. The dense aluminum silicate film layer and the dense silicon oxide film layer of the present application adopt a special coating method, rather than the conventional aluminum silicate coating and silicon oxide coating. If aluminum silicate coating and silicon oxide coating are performed separately, aluminum silicate coating alone is easy to nucleate itself and is not easy to coat on the surface of titanium dioxide, resulting in poor dispersibility and weather resistance. If silicon oxide coating is performed alone, a large amount of silicon dioxide is required to achieve the effect of the three-layer film of this patent, resulting in excessive use of silicate sources such as sodium silicate, which in turn leads to a reduction in the titanium content in the product, and the hiding power and hue of the product cannot meet the requirements.

[0043] Preferably, the amount of silicate source used is 0.5-3.2% of the mass of the titanium dioxide substrate, calculated as silicon dioxide; the amount of aluminum source used is 0.1-1.5% of the mass of the titanium dioxide substrate, calculated as aluminum oxide; the amount of aluminum source and silicate source used is controlled to be ≤0.56 in terms of the Al2O3:SiO2 mass ratio, so that an appropriate amount of silicate source is freely deposited as a silicon oxide film layer.

[0044] Preferably, the pH of the aluminum source and excess silicate source in co-flow is maintained at 9.3-10.2. For sufficient aging, the pH of aluminum silicate aging deposition is 9.6-10.2; the pH of silicon oxide deposition is 5.0-7.0.

[0045] Preferably, the byerite and boehmite composite alumina film layer is formed by the following steps: adding an aluminum source to a titanium dioxide-based material slurry coated with an outer layer of active dense silicon oxide film layer having hydroxyl groups, a dense aluminum silicate film layer, and a dense silicon oxide film layer, adjusting the pH to deposit byerite-type alumina, and then adjusting the pH to deposit boehmite-type alumina to form a byerite and boehmite composite alumina film layer; the amount of aluminum source used is ≤0.9% of the mass of the titanium dioxide substrate in terms of alumina.

[0046] To improve product dispersibility in fluorocarbon coating systems, a high aluminum oxide coating is often required for the outermost layer, typically ≥2.0% aluminum oxide. However, this application utilizes multi-step aluminum oxide deposition to form a composite aluminum oxide film composed primarily of a high-hydroxyl content Bayerite aluminum oxide layer supplemented by a boehmite-type aluminum oxide layer, achieving a total aluminum coating of ≤0.9%. Bayerite, with its three surface hydroxyl groups, is more active, allowing for high dispersibility even with reduced aluminum coating. This reduction in aluminum content increases the titanium content in the product, resulting in superior hiding power and color compared to products with higher aluminum content.

[0047] Preferably, the pH of the Bayerite-type alumina deposition is 9.5-11.7, and the pH of the boehmite-type alumina deposition is 7.0-8.5. The Bayerite and boehmite composite alumina film coating is carried out at 45-65°C. Too high a coating temperature can easily lead to slurry viscosity, which is not conducive to the coating of alumina.

[0048] The present application provides a method for preparing the above-mentioned titanium dioxide for fluorocarbon coatings, comprising the following steps:

[0049] Take titanium dioxide-based material slurry and coat it with an outer layer of active dense silicon oxide film layer with hydroxyl group, a dense aluminum silicate film layer, a dense silicon oxide film layer, and a Bayerite and boehmite composite aluminum oxide film layer in sequence to obtain titanium dioxide for fluorocarbon coating.

[0050] Specifically, the above steps further include:

[0051] S1. Prepare a titanium dioxide-based material slurry, adjust the temperature to 90-98°C, add a pH adjuster to 9.5-10.6, and homogenize for 60-90 minutes; add a silicate source, the amount of which, calculated as silica, is 1.2-1.8% of the mass of the titanium dioxide substrate, and add for 15-45 minutes, followed by homogenization for 60-90 minutes; then adjust the pH to 9.3-9.5 with dilute acid for 40-90 minutes, and homogenize for 40-60 minutes to form an active, dense silicon oxide film with hydroxyl groups on the outer layer; the titanium dioxide-based material slurry can be prepared using either a sulfuric acid method or a chloride method, with a slurry concentration of 220-390 g / L and a 600-mesh sieve residue of less than 0.1%. The pH adjuster is an alkaline mixed solution, which is a mixture of 160-280 g / L sodium hydroxide solution and 1% ammonia solution, with a volume ratio of 9:1-100:1. The silicic acid source is preferably sodium silicate and / or potassium silicate, which are added in the form of a solution at a concentration of 150 to 250 g / L based on silicon oxide. The pH regulator of the present application adopts an alkaline mixed solution, in which ammonia water is weakly alkaline and can play a buffering role in the system, making the pH of the system more stable and not prone to self-precipitation of the coating agent. However, if ammonia water is used alone, the pH is difficult to increase due to its weak alkalinity, so a certain amount of strong alkaline solution is used in combination. Using a strong alkaline solution such as sodium hydroxide alone has no buffering effect, and the coating material is prone to self-precipitation.

[0052] S2. Add aluminum source and silicate source in parallel, the amount of silicate source calculated as silicon dioxide is 0.5-3.2% of the mass of the titanium dioxide substrate; the amount of aluminum source calculated as alumina is 0.1-1.5% of the mass of the titanium dioxide substrate, and the amount of aluminum source and silicate source is controlled to be ≤0.56 in terms of the mass ratio of Al2O3:SiO2, and the parallel pH is maintained at 9.3-10.2. The aluminum source and silicate source are added in parallel for 40-80 minutes, and homogenized for 30-90 minutes after addition; then dilute alkali is added to adjust the pH to 9.6-10.2, the adjustment time is 20-80 minutes, and a dense aluminum silicate film layer is formed after homogenization for 40-60 minutes. The silicic acid source is the same as step S1. Since sodium silicate and potassium silicate are both alkaline, the aluminum source is preferably an acidic aluminum source, which can better maintain the co-current pH. The acidic aluminum source is preferably an aluminum sulfate solution, an aluminum chloride solution or an aluminum nitrate solution, and the concentration is 100-150 g / L in terms of alumina.

[0053] S3. Add dilute acid to adjust the pH to 5.0-7.0 for 60-150 min. After homogenization for 40-90 min, the unreacted silicic acid source in step S2 is deposited to form a dense silicon oxide film.

[0054] S4. Cool the slurry to 45-65°C, add an aluminum source, and adjust the pH to 9.5-11.7. Since the slurry in step S3 is acidic, the aluminum source is preferably alkaline, such as sodium metaaluminate and / or potassium metaaluminate. The slurry pH can be directly adjusted to alkaline. The pH adjustment time is 20-40 minutes, followed by homogenization for 30-80 minutes. Dilute acid is then added to adjust the pH to 7.0-8.5 for 30-60 minutes. Homogenization is then performed again for 30-80 minutes to form a byerite and boehmite composite aluminum oxide film. The amount of aluminum source, calculated as aluminum oxide, is ≤ 0.9% of the mass of the titanium dioxide substrate. The aluminum source is preferably added as a solution at a concentration of 150-200 g / L, calculated as aluminum oxide.

[0055] S5. After coating, the pH is adjusted to 6.5-7.5 with dilute acid, followed by water washing, flash evaporation, steam powdering, and finished product packaging. Finally, the slurry is adjusted to a neutral state, meeting the requirements of downstream products and suitable for use in fluorocarbon coating systems.

[0056] The dilute acid in the above steps is preferably one or both of dilute sulfuric acid and dilute hydrochloric acid, with a concentration of 100 to 140 g / L.

[0057] Example 1

[0058] Take the sulfuric acid base material concentration of 390g / L, 600 mesh sieve residue <0.1%, heat to 98°C, use mixed alkali solution (a mixture of 280g / L sodium hydroxide solution and 1% ammonia solution, the mixing volume ratio is 100:1) to adjust the pH to 10.6, and homogenize for 90min; add 1.8% of 250g / L sodium silicate solution to the slurry, add time 45min, homogenize for 90min; adjust the pH to 9.5 with 140g / L dilute sulfuric acid, adjust time 90min, homogenize for 60min; add 1.5% of 150g / L aluminum sulfate and 3.2% of 200g / L potassium silicate solution in parallel, maintain pH at 10.2, add time 80min, homogenize time 90min; then use dilute sodium hydroxide solution to adjust the pH to 10.2 (as the homogenization proceeds, the pH may change, therefore, it is necessary to adjust the pH to 10.2 again), the adjustment time 80min, and the homogenization 60min; then use dilute sulfuric acid solution to adjust the pH to 7.0, the addition time 150min, and the homogenization 90min; cool to 65°C, add 0.9% sodium aluminate solution with a concentration of 200g / L, adjust the pH to 11.7, the addition time 40min, and the homogenization time 80min; use dilute sulfuric acid to adjust the pH to 8.5, the addition time 60min, and the homogenization time 80min; again use dilute sulfuric acid to adjust the pH to 7.5, carry out water washing, flash evaporation, steam powder and finished product packaging to obtain sample 1.

[0059] Example 2

[0060] Take the sulfuric acid base material concentration of 290g / L, 600 mesh sieve residue <0.1%, heat to 90℃, use mixed alkali solution (a mixture of 160g / L sodium hydroxide solution and 1% ammonia solution, the mixing volume ratio is 9:1) to adjust and maintain at 9.5, and homogenize for 60min; add 1.2% 150g / L sodium silicate solution to the slurry, add time 15min, homogenize for 60min; adjust the pH to 9.3 with 100g / L dilute sulfuric acid, adjust time 40min, homogenize for 40min; add 0.1% 100g / L aluminum sulfate and 0.5% 150g / L potassium silicate solution in parallel, maintain the pH at 9.3, adding time 40min, homogenizing time 30min; then using dilute sodium hydroxide solution to adjust the pH to 9.6, adjusting time 20min, and homogenizing for 40min; then using dilute sulfuric acid solution to adjust the pH to 5.0, adding time 60min, and homogenizing for 40min; cooling to 45°C, adding 0.4% 150g / L sodium aluminate solution, adjusting the pH to 9.5, adding time 20min, and homogenizing time 30min; adjusting the pH to 7.0 with dilute sulfuric acid, adding time 30min, and homogenizing time 30min; adjusting the pH to 6.5 with dilute sulfuric acid again, washing, flash evaporation, steam powder and finished product packaging are carried out to obtain sample 2.

[0061] Example 3

[0062] Take the chloride base material concentration of 300g / L, 600 mesh sieve residue <0.1%, heat to 95°C, use mixed alkali solution (a mixture of 180g / L sodium hydroxide solution and 1% ammonia solution, the mixing volume ratio is 20:1) to adjust and maintain at 9.6, and homogenize for 80min; add 1.5% 200g / L potassium silicate solution to the slurry, add time 30min, homogenize for 80min; adjust the pH to 9.4 with 120g / L dilute sulfuric acid solution, adjust time 60min, homogenize for 50min; add 0.8% 100g / L aluminum sulfate and 1.5% 150g / L potassium silicate solution in parallel, maintain p H is 9.5, the addition time is 60 minutes, and the homogenization time is 60 minutes; then dilute sodium hydroxide solution is added to adjust the pH to 9.8, the adjustment time is 30 minutes, and the homogenization time is 50 minutes; then dilute sulfuric acid solution is used to adjust the pH to 6.0, the addition time is 80 minutes, and the homogenization time is 60 minutes; the temperature is lowered to 55°C, 0.8% sodium aluminate solution with a concentration of 170g / L is added, the pH is adjusted to 9.8, the addition time is 30 minutes, and the homogenization time is 50 minutes; the pH is adjusted to 8.0 with dilute sulfuric acid, the addition time is 40 minutes, and the homogenization time is 40 minutes; the pH is adjusted to 7.0 with dilute sulfuric acid again, and water washing, flash evaporation, steam powder and finished product packaging are carried out to obtain sample 3.

[0063] Example 4

[0064] Take the chloride base material concentration of 320g / L, 600 mesh sieve residue <0.1%, heat to 94°C, use mixed alkali solution (a mixture of 200g / L sodium hydroxide solution and 1% ammonia solution, the mixing volume ratio is 45:1) to adjust and maintain at 9.9, and homogenize for 80min; add 1.5% 200g / L sodium silicate solution to the slurry, add time 30min, homogenize for 80min; adjust the pH to 9.5 with 100g / L dilute sulfuric acid solution, adjust time 60min, homogenize for 50min; add 1.0% 100g / L aluminum nitrate and 2.2% 150g / L potassium silicate solution in parallel, maintain pH The pH value is 9.5, the addition time is 60 minutes, and the homogenization time is 60 minutes; then, dilute sodium hydroxide solution is used to adjust the pH value to 10.0, the adjustment time is 30 minutes, and the homogenization time is 50 minutes; then, dilute sulfuric acid solution is used to adjust the pH value to 6.0, the addition time is 80 minutes, and the homogenization time is 60 minutes; the temperature is lowered to 55°C, 0.8% sodium aluminate solution with a concentration of 170g / L is added, the pH value is adjusted to 9.8, the addition time is 30 minutes, and the homogenization time is 50 minutes; the pH value is adjusted to 8.0 with dilute sulfuric acid, the addition time is 40 minutes, and the homogenization time is 40 minutes; the pH value is adjusted to 6.5 with dilute sulfuric acid again, and water washing, flash evaporation, steam powder and finished product packaging are carried out to obtain sample 4.

[0065] Example 5

[0066] Take the chloride base material concentration of 300g / L, 600 mesh sieve residue <0.1%, heat to 94°C, use mixed alkali solution (a mixture of 200g / L sodium hydroxide solution and 1% ammonia solution, the mixing volume ratio is 65:1) to adjust and maintain at 10.5, and homogenize for 80min; add 1.2% 200g / L potassium silicate solution to the slurry, add time 30min, homogenize for 80min; adjust the pH to 9.5 with a concentration of 140g / L dilute sulfuric acid solution, adjust time 60min, homogenize for 50min; add 1.0% 100g / L aluminum chloride solution and 2.5% 150g / L potassium silicate solution in parallel, maintain The pH value was 9.5, the addition time was 60 min, and the homogenization time was 60 min; then, a dilute sodium hydroxide solution was used to adjust the pH value to 10.0, the adjustment time was 30 min, and the homogenization time was 50 min; the pH value was then adjusted to 6.0 with a dilute sulfuric acid solution, the addition time was 80 min, and the homogenization time was 60 min; the temperature was lowered by 55°C, 0.6% sodium aluminate solution with a concentration of 200 g / L was added, the pH value was adjusted to 10.3, the addition time was 30 min, and the homogenization time was 50 min; the pH value was adjusted to 8.0 with dilute sulfuric acid, the addition time was 40 min, and the homogenization time was 40 min; the pH value was adjusted to 6.5 with dilute sulfuric acid again, and water washing, flash evaporation, steam powder and finished product packaging were carried out to obtain sample 5.

[0067] Example 6

[0068] Take the chloride base material concentration of 320g / L, 600 mesh sieve residue <0.1%, heat to 94°C, use mixed alkali solution (a mixture of 200g / L sodium hydroxide solution and 1% ammonia solution, the mixing volume ratio is 85:1) to adjust and maintain at 10.4, and homogenize for 80min; add 1.3% 200g / L sodium silicate solution to the slurry, add time 30min, homogenize for 80min; adjust the pH to 9.5 with 100g / L dilute sulfuric acid solution, adjust time 60min, homogenize for 50min; add 0.9% 100g / L aluminum nitrate and 2.4% 150g / L potassium silicate solution in parallel, maintain pH The pH value is 9.5, the addition time is 60 minutes, and the homogenization time is 60 minutes; then, dilute sodium hydroxide solution is used to adjust the pH value to 10.0, the adjustment time is 30 minutes, and the homogenization time is 50 minutes; then, dilute sulfuric acid solution is used to adjust the pH value to 6.0, the addition time is 80 minutes, and the homogenization time is 60 minutes; the temperature is lowered to 55°C, 0.9% sodium aluminate solution with a concentration of 170g / L is added, the pH value is adjusted to 11.5, the addition time is 30 minutes, and the homogenization time is 50 minutes; the pH value is adjusted to 8.0 with dilute sulfuric acid, the addition time is 40 minutes, and the homogenization time is 40 minutes; the pH value is adjusted to 6.5 with dilute sulfuric acid again, and water washing, flash evaporation, steam powder and finished product packaging are carried out to obtain sample 6.

[0069] Comparative Example 1

[0070] The sulfuric acid base material concentration is 390 g / L, the 600 mesh sieve residue is less than 0.1%, the temperature is raised to 98°C, the sodium hydroxide solution is adjusted to 10.6, and the slurry is homogenized for 90 minutes; 5.0% of a 250 g / L sodium silicate solution is added to the slurry for 45 minutes and the slurry is homogenized for 90 minutes; the pH is adjusted to 7.0 with a concentration of 140 g / L dilute sulfuric acid for 90 minutes and the slurry is homogenized for 60 minutes; 3.5% of a 150 g / L sodium aluminate solution is added in parallel with the sulfuric acid, the parallel flow pH is 7.5-8.5, the addition time is 60 minutes, and the homogenization time is 80 minutes; the pH is adjusted to 7.5 with dilute sulfuric acid, and the slurry is washed with water, flash evaporated, steam-powdered and packaged as a finished product to obtain a comparative sample 1.

[0071] Comparative Example 2

[0072] The chloride base material concentration is 390 g / L, the 600 mesh sieve residue is less than 0.1%, the temperature is raised to 98°C, the sodium hydroxide solution is adjusted to 10.6, and the slurry is homogenized for 90 minutes; 5.0% of a 250 g / L sodium silicate solution is added to the slurry for 45 minutes and the slurry is homogenized for 90 minutes; the pH is adjusted to 7.0 with 140 g / L dilute sulfuric acid for 90 minutes and the slurry is homogenized for 60 minutes; 3.5% of a 150 g / L sodium aluminate solution is added in parallel with the sulfuric acid to a pH of 7.5-8.5, the addition time is 60 minutes, and the homogenization time is 80 minutes; the pH is adjusted to 7.5 with dilute sulfuric acid, and the slurry is washed with water, flash evaporated, steam-powdered and packaged as a finished product to obtain a comparative sample 2.

[0073] The performance of the comparative examples and example samples was evaluated using conventional methods, and the results are shown in Tables 1 and 2.

[0074] Table 1 Sample production data and physical and chemical properties test

[0075] Sample name L b Dispersion / micron Comparison 1 96.4 0.89 35 Comparison 2 97.2 0.86 35 Sample 1 98.3 0.67 25 Sample 2 98.1 0.64 20 Sample 3 99.0 0.60 20 Sample 4 98.9 0.69 20 Sample 5 99.2 0.64 20 Sample 6 99.3 0.78 15

[0076] Table 2 Weathering resistance test data of samples in fluorocarbon system

[0077]

[0078] As shown in Tables 1 and 2, the titanium dioxide prepared in the present invention has extremely high whiteness and weather resistance compared with the comparative samples. Combined with the electron microscope images attached below, it is found that the titanium dioxide coating layer prepared in Comparative Example 1 is loose and uneven, and the coating layer of Comparative Example 2 has self-nucleation ( Figure 8 The white area in the circle), while the titanium dioxide coating layer obtained in Examples 1 to 6 of the present application is uniform and dense, indicating that the titanium dioxide silicon aluminum film layer prepared by the present invention is uniform, dense and continuous, and can be used for fluorocarbon coatings to provide extremely high hue and weather resistance. The present invention solves the problem that hue and weather resistance cannot be taken into account at the same time.

[0079] Although preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic inventive concepts. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the invention. Thus, the present invention is intended to include such changes and modifications as fall within the scope of the claims and their equivalents.

Claims

1. A titanium dioxide for fluorocarbon coating, characterized in that: It comprises a titanium dioxide substrate and a coating layer located on the surface of the titanium dioxide substrate, wherein the coating layer comprises, from the inside to the outside, an outer layer of an active dense silicon oxide film layer having hydroxyl groups, a dense aluminum silicate film layer, a dense silicon oxide film layer, and a byerite and boehmite composite aluminum oxide film layer; The dense aluminum silicate film layer and the dense silicon oxide film layer are formed by the following steps: an aluminum source and an excess of a silicate source are added in parallel to a titanium dioxide-based material slurry that covers the outer layer of the active dense silicon oxide film layer having hydroxyl groups, and then the pH is adjusted to ripen and deposit the aluminum silicate to form a dense aluminum silicate film layer; the incompletely reacted silicate source is adjusted by pH again to deposit silicon oxide to form the dense silicon oxide film layer.

2. The titanium dioxide for fluorocarbon coating according to claim 1, characterized in that: The outer layer of active dense silicon oxide film with hydroxyl groups is formed by the following steps: adding a silicate source to a titanium dioxide-based material slurry at a temperature of 90 to 98°C and a pH of 9.5 to 10.6, then adjusting the pH to 9.3 to 9.5, and forming the outer layer of active dense silicon oxide film with hydroxyl groups after homogenization.

3. The titanium dioxide for fluorocarbon coating according to claim 2, characterized in that: The amount of the silicic acid source used is 1.2-1.8% of the mass of the titanium dioxide substrate, calculated as silicon dioxide.

4. The titanium dioxide for fluorocarbon coatings according to claim 1, characterized in that: The amount of the silicate source used for coating the dense aluminum silicate film layer and the dense silicon oxide film layer is 0.5-3.2% of the mass of the titanium dioxide substrate in terms of silicon dioxide; the amount of the aluminum source used is 0.1-1.5% of the mass of the titanium dioxide substrate in terms of aluminum oxide.

5. The titanium dioxide for fluorocarbon coating according to claim 1, characterized in that: The amount of the aluminum source and the silicate source used for coating the dense aluminum silicate film layer and the dense silicon oxide film layer is ≤0.56 in terms of the mass ratio of Al2O3:SiO2.

6. The titanium dioxide for fluorocarbon coating according to claim 1, characterized in that: The pH of the aluminum source and excess silicate source flowing in parallel for coating the dense aluminum silicate film layer and the dense silicon oxide film layer is maintained at 9.3-10.2, the aluminum silicate aging pH is 9.6-10.2; and the silicon oxide deposition pH is 5.0-7.

0.

7. The titanium dioxide for fluorocarbon coating according to claim 1, characterized in that: The Bayerite and boehmite composite aluminum oxide film layer is formed by the following steps: adding an aluminum source to a titanium dioxide-based material slurry coated with the outer layer of active dense silicon oxide film layer with hydroxyl groups, a dense aluminum silicate film layer, and a dense silicon oxide film layer, adjusting the pH to deposit Bayerite-type aluminum oxide, and then adjusting the pH to deposit boehmite-type aluminum oxide to form the Bayerite and boehmite composite aluminum oxide film layer; the amount of the aluminum source used is ≤0.9% of the mass of the titanium dioxide substrate in terms of alumina.

8. The titanium dioxide for fluorocarbon coating according to claim 7, characterized in that: The pH of the Bayerite-type aluminum oxide deposition is 9.5-11.7, and the pH of the boehmite-type aluminum oxide deposition is 7.0-8.5; the Bayerite and boehmite composite aluminum oxide film coating is carried out at 45-65°C.

9. The method for preparing titanium dioxide for fluorocarbon coatings according to any one of claims 1 to 8, characterized in that: The following steps are involved: Taking titanium dioxide-based material slurry, coating the outer layer with an active dense silicon oxide film layer having hydroxyl groups, a dense aluminum silicate film layer, a dense silicon oxide film layer, and a Bayerite and boehmite composite aluminum oxide film layer in sequence to obtain the titanium dioxide for fluorocarbon coatings; The coating method of the dense aluminum silicate film layer and the dense silicon oxide film layer is as follows: in the titanium dioxide-based material slurry coating the outer layer of active dense silicon oxide film layer having hydroxyl groups, an aluminum source and an excess silicate source are added in parallel, and then the pH is adjusted to ripen and deposit the aluminum silicate to form a dense aluminum silicate film layer; the silicate source that has not reacted completely is adjusted to pH again to deposit silicon oxide to form the dense silicon oxide film layer.

10. The method for preparing titanium dioxide for fluorocarbon coatings according to claim 9, characterized in that: The coating method of the active dense silicon oxide film layer having hydroxyl groups on the outer layer is as follows: adding a silicate source to a titanium dioxide-based material slurry at a temperature of 90 to 98° C. and a pH of 9.5 to 10.6, then adjusting the pH to 9.3 to 9.5, and forming the active dense silicon oxide film layer having hydroxyl groups on the outer layer after homogenization; The coating method of the Bayerite and boehmite composite aluminum oxide film layer is as follows: adding an aluminum source to a titanium dioxide-based material slurry coated with the outer layer of active dense silicon oxide film layer with hydroxyl groups, dense aluminum silicate film layer, and dense silicon oxide film layer, adjusting the pH to deposit Bayerite-type aluminum oxide, and then adjusting the pH to deposit boehmite-type aluminum oxide to form the Bayerite and boehmite composite aluminum oxide film layer; the amount of the aluminum source used is ≤0.9% of the mass of the titanium dioxide substrate in terms of alumina.

11. The method for preparing titanium dioxide for fluorocarbon coatings according to claim 9, characterized in that: The preparation method further comprises: S1. Take a titanium dioxide-based material slurry, adjust the temperature to 90-98°C and the pH to 9.5-10.6; add a silicate source, then adjust the pH to 9.3-9.5, and form an active dense silicon oxide film layer with hydroxyl groups on the outer layer after homogenization; S2. Adding an aluminum source and a silicate source in parallel, wherein the amount of the aluminum source and the silicate source is based on a mass ratio of Al2O3:SiO2 of ≤0.56, maintaining the pH of the parallel flow at 9.3 to 10.2, and then adjusting the pH to 9.6 to 10.2, and forming a dense aluminum silicate film layer after homogenization; S3. Adjust the pH to 5.0-7.0, and after homogenization, the unreacted silicic acid source in step S2 is deposited to form a dense silicon oxide film layer; S4. Add an aluminum source, adjust the pH to 9.5-11.7, adjust the pH to 7.0-8.5 after homogenization, and form a composite aluminum oxide film layer of bayerite and boehmite after homogenization again; the amount of the aluminum source used is ≤0.9% of the mass of the titanium dioxide substrate in terms of alumina.

Citation Information

Patent Citations

  • Preparation method of titanium dioxide pigment with high covering power, weather resistance and whiteness

    CN106497147A

  • Preparation method for titanium dioxide special for printing ink

    CN109535775A